Aplicación del método de flexibilidad activa en el rango de movilidad articular del tren inferior de los deportistas de 10 – 12 años que practican taekwondo en la Unidad Educativa Once de Noviembre periodo 2018 – 2019 - Guzmán Tanqueño, Fausto Daniel (2019)
Explained the methodological changes in the range of joint mobility of the lower body through the methodological intervention of the Active Flexibility Method through the use of Elastic Bands (Theraband), as a means of developing and perfecting a specific capacity in a combat sport. The research presented a quasi - experimental quantitative approach with an experimental group and a control group by establishing caused - affect relationships of an active flexibility training program of 12 weeks of training. The study population comprised 40 subjects between 10 and 12 years of age 20 corresponding to the control group and 20 to the uncontrolled group distributed by simple random sampling. Once the intervention was concluded, it was possible to verify by means of a post test an improvement in the radius of action that is capable of producing an articulation, and through the t test it was possible to establish significant differences in each of the tests carried out. It is concluded that alternative training methods improve flexibility, which is why the influence of a training method on the development of a physical capacity (flexibility) is discussed, through the use of assisted techniques supported by contemporary implements.